2019
DOI: 10.1002/wps.20632
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of oral second‐generation antipsychotics in patients with schizophrenia and related disorders: a systematic review and meta‐analysis of direct head‐to‐head comparisons

Abstract: Second-generation antipsychotics (SGAs) are recommended for maintenance treatment in schizophrenia. However, comparative long-term effectiveness among SGAs is unclear. Here we provide a systematic review and meta-analysis of randomized trials lasting ≥6 months comparing SGAs head-to-head in schizophrenia and related disorders. The primary outcome was all-cause discontinuation. Secondary outcomes included efficacy and tolerability, i.e., psychopathology, inefficacy-related and intolerability-related discontinua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 95 publications
(98 reference statements)
4
76
0
1
Order By: Relevance
“…However, the evidence of this effect is contradictory since there is also proof of the decrease during the consumption of this drug. It has been reported that according to the period of consumption, the effects on PRL blood levels change (111,198,199): The consumption during short periods (<2 weeks) or the intake of a single dose does not alter PRL levels (111,200).…”
Section: Olanzapinementioning
confidence: 99%
“…However, the evidence of this effect is contradictory since there is also proof of the decrease during the consumption of this drug. It has been reported that according to the period of consumption, the effects on PRL blood levels change (111,198,199): The consumption during short periods (<2 weeks) or the intake of a single dose does not alter PRL levels (111,200).…”
Section: Olanzapinementioning
confidence: 99%
“…Of 20 antipsychotic medications that significantly lowered discontinuation rates compared with placebo, amisulpride, olanzapine, paliperidone, and clozapine were amongst those with the lowest rates of all-cause discontinuation, whereas haloperidol was the highest [6]. Focusing exclusively on direct comparisons of SGAs, a separate meta-analysis supported these findings, identifying clozapine, olanzapine, and risperidone as superior to several other SGAs, whereas quetiapine was inferior to several [12].…”
Section: Effectivenessmentioning
confidence: 89%
“…The bulk of evidence from meta-analyses on antipsychotic medications have established three 'tiers' of efficacy: 1) clozapine has consistently demonstrated superiority over other treatment options, 2) olanzapine, risperidone, and amisulpride are significantly more efficacious than FGAs and most other SGAs, and 3) the remaining antipsychotics are similarly efficacious [5,6,12]. Some evidence suggests that quetiapine and ziprasidone may be inferior to some other SGAs, though quetiapine is often under dosed due to sedation [12].…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Dopamine modulating antipsychotics remain the primary and only currently approved treatment for schizophrenia, and over the past years many different antipsychotics have been developed and tested for their efficacy and safety in reducing acute symptoms of schizophrenia and maintaining stability. [5][6][7][8][9] However, currently available drugs are mostly effective against positive symptoms (i.e., hallucinations, delusions, disorganized thought or speech, and bizarre behaviors). This situation leaves most patients with diverse residual symptoms relatively untreated, especially negative symptoms (lack of motivation, drive, enjoyment, social interactions) and cognitive dysfunction (deficits in attention, memory, executive functioning, grasp of social situations/interactions), which lead to poor quality of life outcomes and lifelong impairments, [10][11][12][13][14][15][16][17][18] as cognitive and negative symptoms persist for most of the patients' lives.…”
Section: Introductionmentioning
confidence: 99%